Mechanical and thermal properties of crab chitin reinforced carboxylated SBR composites - C. Santulli; P. M. Visakh; S. Thomas; M. Monti; M. Rallini; D. Puglia; F. Sarasini; J. M. Kenny (eXPRESS Polymer Letters, 2012)
The addition of small amounts (up to 9 wt%) of chitin microsized particles, originating from shellfish waste, to carboxylated styrene-butadiene rubber (XSBR) matrix (as received and annealed to 100°C) has been studied. In particular, this study concentrated on their mechanical (creep investigation by nanoindentation and dynamical-mechanical analysis), thermal (differential scanning calorimetry and thermogravimetry) and swelling behaviour (toluene absorption) and was completed by morphological characterisation by scanning electron microscopy and atomic force microscopy. The results show that annealing has a limited effect on materials properties, effects which are further reduced by the addition of growing amounts of crab chitin. It should be noted that the limited filler content used in the study does not substantially modify the linear creep behaviour of XSBR for sufficiently long loading times. The thermal stability of the system does also appear to be preserved even with the maximum chitin content added, while it serves sufficiently as an effective barrier against aromatic solvent absorption.